SPATIAL ABILITY IN MIDDLE SCHOOL MATHEMATICS LEARNING: SYSTEMATIC LITERATURE REVIEW (SLR) - Ena, Candra; Prabawanto , Sufyani; Juandi , Dadang; Sugiarni, Rani (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2023)
Spatial ability is the cognitive process of seeing an item and building relationships between that item and its surroundings. This ability is an important element in learning mathematics that can be applied to various problems in life. The purpose of this study was to analyze published articles on spatial abilities from 2012 to 2022. This research uses the Systematic Literature Review (SLR) method which is used to collect primary data related to spatial abilities published on the Google Scholar search engine. Data selection was based on the journal index, year of publication, education level, sample size, research location, and research materials. From the research results, it was found that the most published research was in 2018 and the most applied to geometry teaching materials. The results also show that most research on spatial abilities is conducted on the island of Java at the junior high school level. From this study it is also recommended that similar research be carried out outside Java and use elementary, high school, university levels, and also use statistics, algebra, and arithmetic materials.